2011
DOI: 10.1371/journal.pone.0018689
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of IL-34 in Osteoclastogenesis

Abstract: It has been widely believed that the cytokines required for osteoclast formation are M-CSF (also known as CSF-1) and RANKL. Recently, a novel cytokine, designated IL-34, has been identified as another ligand of CSF1R. This study was to explore the biological function, specifically osteoclastogenesis and bone metabolism, of the new cytokine. We produced recombinant mouse IL-34 and found that together with RANKL it induces the formation of osteoclasts both from splenocytes as well as dose-dependently from bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 30 publications
(39 reference statements)
4
114
0
Order By: Relevance
“…The recently discovered cytokine IL-34 is an alternative ligand for the M-CSF receptor, and is now considered to constitute a novel non-canonical pathway of osteoclast formation, as it can substitute for M-CSF in osteoclast differentiation and play an important role in RANKL-induced osteoclastogenesis 9) . Patients with inflammatory periodontal disease often have elevated serum levels of proinflammatory cytokines 19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently discovered cytokine IL-34 is an alternative ligand for the M-CSF receptor, and is now considered to constitute a novel non-canonical pathway of osteoclast formation, as it can substitute for M-CSF in osteoclast differentiation and play an important role in RANKL-induced osteoclastogenesis 9) . Patients with inflammatory periodontal disease often have elevated serum levels of proinflammatory cytokines 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-34 plays an important role in RANKL-induced osteoclastogenesis, as it can substitute for M-CSF and support osteoclast differentiation in the same way 9) . It is likely that IL-34 plays a role in inflammation, as it increases IL-6 and chemokine levels in human whole blood 11) .…”
Section: Introductionmentioning
confidence: 99%
“…When IL-34 was expressed under the control of the CSF-1 promotor in CSF-1 op/op mice, the osteopetrotic phenotype was rescued (15). IL-34 in combination with RANKL induced osteoclastic differentiation of progenitor cells in mouse (16,17) and human (17) cell culture systems. However, it remains unclear why IL-34 cannot substitute for CSF-1 in CSF-1 op/op mice in vivo.…”
Section: ] (1 2)mentioning
confidence: 99%
“…Eda et al, documented that IL-34 could increase IL-6 and chemokine levels in human whole blood [12]. It also could promote osteoclastogenesis in vitro [13]. Tian et al, found that IL-34 expression could be induced by TNF-α and IL-1β which are pivotal cytokines in RA [14].…”
Section: Introductionmentioning
confidence: 99%